Effect of Human Platelet Lysate in Differentiation of Wharton’s Jelly Derived Mesenchymal Stem Cells - Vennila, Rosy; Sundaram, Raja Sundari M.; Selvaraj, Sakthivel; Srinivasan, Prasanna; Pathak, Surajit; Rupert, Secunda; Rajagopal, Surendran (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background: Mesenchymal stem cells (MSCs) are highly preferred in clinical therapy for repair and regeneration of diseased tissues for their multipotent properties. Conventionally, MSCs have been cultured in media supplemented with animal derived serum, however, it is ideal to expand MSCs in media containing supplements of human origin for clinical therapy. Currently, a number of human derived products are being studied as an alternative to animal sources. Amongst these, platelet lysate (PL) has gained interest in the culture of MSCs without affecting their phenotypic property. Objective: In this study, we used various concentration of PL (2.5, 5, 7.5 & 10%) in the growth medium of MSCs to identify the least concentration of PL that could be an effective alternative to animal products. Methods: MSCs were isolated from Wharton’s Jelly by using explant method and expanded in various concentration of PL supplemented medium against the standard FBS containing medium. WJ-MSCs were characterised as per the minimal criteria proposed by International Society for Cell therapy (ISCT), Proliferation study by BrdU assay, gene expression study by qRT-PCR, sterility test for bacteria, Mycoplasma by PCR and endotoxin detection by LAL assay. Results: Whartons jelly derived MSCs (WJ-MSCs) cultured using standard medium supplemented with various concentration of PL exhibited enhanced proliferation and differentiation potential, unaltered immunophenotypic property and genetic stability when compared with the commercial medium containing 10% FBS. Conclusion: The least concentration of PL for an ideal expansion of MSCs was found to be 2.5% and was comparable to FBS.
Keywords: Platelet lysate